2015
DOI: 10.3390/ijerph120605758
|View full text |Cite
|
Sign up to set email alerts
|

Are Women in Turkey Both Risks and Resources in Disaster Management?

Abstract: From a global perspective, the universality of gender-related societal issues is particularly significant. Although gender inequality is considered a sociological problem, the large number of female victims in disasters warrants an assessment of disaster management sciences. In this article, related concepts are discussed based on their relevance sociologically and in disaster management to develop a common terminology and examine this complex topic, which is rooted in different social profiles and anthropolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…This result suggests that SWB of local older residents living in their own residences is affected by the same previously reported predictors. Moreover, a previous study reported that women are more vulnerable during disasters compared to men because of genetic, psychological, physiological, and social factors [48], and that women living in affected areas after the GEJE were more likely to suffer from mental health problems [40]. On the other hand, residents of RPH have moved several times, which was more stressful for them.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that SWB of local older residents living in their own residences is affected by the same previously reported predictors. Moreover, a previous study reported that women are more vulnerable during disasters compared to men because of genetic, psychological, physiological, and social factors [48], and that women living in affected areas after the GEJE were more likely to suffer from mental health problems [40]. On the other hand, residents of RPH have moved several times, which was more stressful for them.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the importance of the establishment of specifi c policies and laws for preserving the mental health of women has been emphasized in studies. [5,9,14,26] Other factors that were in the next degree of importance, however with very little degree of difference to the previous ones, included psychological well-being through treatment of mental disorders (treatment of mental disorders including anxiety, depression, PTSD, fear of injury, shock, imagination of death and disaster, tendency toward self-harm, suicidal thoughts), dignity and position of women in situations of harm (social value of women in disasters, key role of women in the damaged family, role of women as levers in events, maternity role, the spouse role, women's participation in society), nutrition and physical activities during disasters (healthy nutrition, nutritional problems in crisis, preservation of food for emergencies, women's nutrition in certain physical conditions, suitable activities in less-equipped places, exercising in limited conditions, appropriate physical activities for physical damages), role and responsibilities of women in crisis (lack of abuse of women in multiple responsibilities, suitable attention to the simultaneous spouse-mother role of women, inconsistency between women's efforts and the outcomes, suitable participation of women in constructional development, overburden in difficult conditions), health-seeking behaviors during disasters (body care under damage conditions, making health claims, awareness of observance of health issues, feeling responsible for their own health and that of others, access to health services in special circumstances), awareness of high-risk behavioral habits (smoking, alcohol use under stress, risky sexual behaviors, drug abuse, coping with unsuitable behavioral habits in crisis), learning skills and gaining experiences (familiarity with incomegenerating jobs, training applied skills like tailoring, driving, building, swimming, carpet weaving, making handicrafts, dairying, and etc., self-help, learning how to provide for the family as a householder), and governing culture in the disaster area (respect for the culture of the region, cultural adaptation of the injured and helpers, cultural constraints of women, consideration of cultural indicators of women of the area when providing assistance, lack of priority of rescuing women due to the governing culture).…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Women are more vulnerable in disasters compared to men due to some genetic, psychological, physiological, legal, and social factors. [5] A study [6] conducted through 33 qualitative interviews with disaster experts in Iran referred to the biological, social, and psychological dimensions of women's vulnerability to disasters. Moreover, another study on the earthquake in East Azarbaijan Province, Iran, pointed to severe poverty and violence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous papers identified gender as a very important factor in determining behavior and recovery after a natural hazard such an earthquake. The Qiang & Zang households followed that conclusion, because women have additional dependencies and household responsibilities, and face greater risks in hazards compared to men in a household [ 63 ].…”
Section: Discussionmentioning
confidence: 99%